파프리카 자조금 제도 운영방식에 대한 생산자선호 분석 - 홍나경 (한국농촌경제연구원, 2012)
This paper analyzes the producers’ preferences for check-off program of paprika using a choice experiment format. A multinomial logit model is estimated using primary data from a survey of paprika producers. The results show that paprika producers are more likely to prefer higher spending for market promotion, higher participation rate, more government subsidy, and lower participation fees. The results also indicate that age, education, export ratio, and acreage are also significant factors explaining farmers’ preferences for check-off program. Based on the results, some policy implications that might contribute to developing a mandatory check-off system of horticultural products were derived.
Keywords: 파프리카; 자조금 제도 생산자선호; 선택형 실험; 다항로짓모형; paprika; check-off program; producers’ preference; choice experiment; multinomial logit model